Ducts of Luschka as a Mimicker of Well-Differentiated Adenocarcinoma of Gallbladder: A Case Report and Review of Literature - He, MD, Jing; Cai, MD, PhD, Zhenjian; Zhu, MD, PhD, Hui (North American Journal of Medicine and Science, 2016)
Ducts of Luschka are small bile ducts located at the subserosal or subhepatic connective tissue of gallbladder. These ducts are commonly seen in up to 10% of routine cholecystectomy specimens. When proliferating with reactive changes as seen in the background of acute cholecystitis, they can mimic adenocarcinoma of gallbladder. However, this phenomenon is not well recognized in pathology literature, with only two articles available in English language literature. In this study, we report a case of acute cholecystitis with reactive Ducts of Luschka that is difficult to distinguish from gallbladder adenocarcinoma. We described the clinical and pathologic findings in this case and discussed the morphologic features that are helpful in establishing the correct diagnosis. [N A J Med Sci. 2016;9(4):187-191. DOI: 10.7156/najms.2016.0904187] Key Words: ducts of Luschka, gallbladder adenocarcinoma